Strategi Guru Pendidikan Agama Islam dalam Pembinaan Akhlakul Karimah Siswa di Sekolah Menengah Pertama - Eda Laelasari; Herlina Herlina; Fidya Farwati; Eva Siti Faridah (STAI Al-Hamidiyah Jakarta, 2024)
Teachers play an important role in the process of fostering the morality of their students, especially religious teachers. For the success of the coaching process, the teacher must be able to use various strategies in shaping morality. This study aims to 1) To find out about the Strategies of Islamic Religious Education Teachers at Al-Muhajirin Islamic Middle School, Gunung Sindur District, Bogor Regency 2) To find out about the Guidance of Morals for Students at Al-Muhajirin Islamic Middle School, Gunung Sindur District, Bogor Regency 3) To find out about the factors that influence the Akhlakul Karimah Development Strategy for students at Al-Muhajirin Islamic Junior High School, Gunung Sindur District, Bogor Regency. The method used in this study uses a descriptive qualitative approach. Data collection techniques used the methods of observation, interviews, and documentation. The data analysis technique used by Miles and Huberman is data reduction, data presentation, and drawing conclusions. The results of the study show, 1) The strategy of Islamic Religious Education Teachers, includes: Personal approach, example, habituation and punishment. 2) Guiding the Morals of Students, there are 3 of them, namely moral development that builds a relationship with Allah SWT by performing mandatory and sunnah worship such as recitations, Duha prayers, Dzuhur prayers in congregation and Berinfaq/sodaqoh. Relationships with others such as smiles, greetings, greetings, behavior, courtesy, mutual respect and appreciation. Relationship with the environment by protecting and caring for the environment. 3) Factors that influence the development of student morality, the first supporting factors for fostering student morality: awareness in students, role models in teachers, learning methods, cooperation and support from parents, facilities and infrastructure. The two inhibiting factors for fostering student morality: Lack of hours of Islamic religious education subjects, misuse of cellphones, student environment.